(untitled) (Global Journal of Management and Business Research, 2018)
Theory of “Productivity of Labour” expounded labour productivity as one of the basic indicators of economic development, the major detriment of national income and important tool for analysis of economic and social problems. Labour productivity is the capital utilization of human resources of a concern. Labour productivity measures efficiency of labour force, which is directly related to savings in this item and since there has always been widespread interest in labour saving, labour productivity has become more popular as well as its importance and utility in the concern. This research paper is based on Labour Productivity Analysis of private sector enterprises. The present study concludes that value generated in the form of output (Productivity) of different private sector enterprises differs from each other.